Customer Purchase Intention on Sharia Mutual Fund Products: A TPB Approach - Evie Octarina; Hartoyo Hartoyo; Irfan Syauqi Beik (Journal of Consumer Sciences, 2019)
This study aimed to determine the influence of variables in TPB (attitude toward behavior, perceived behavioral control, subjective norm), religiosity, knowledge, and risk perception to intention purchase of sharia mutual fund. The sample in this study was customer of Bank Sharia XYZ of 164 customers. The analysis applied in this study was Structural Equation Modeling-Partial Least Square. The result of this research showed that the independent variable had positive and significant influence to dependent variables attitude toward behavior and subjective norm. Religiosity and knowledge have no significant influence toward intention to purchase, while perceived behavioral control and risk perception had no significant influence with intention to purchases. The other result showed that religiosity had a positive significant influence to attitude toward behavior. The conclusion of this research shown that religiosity is the factor which influence attitude toward behavior, attitude toward behavior and subjective norm are the factors which influence intention purchase of sharia mutual fund.